2013
DOI: 10.1111/tmi.12098
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between antenatal provider type and maternal care in rural Ghana: a cross‐sectional study

Abstract: Abstractobjectives To investigate the influence of antenatal provider type on maternity care in rural Ghana. results Thousand and three hundred and sixty-seven rural women reported a live birth. Provider distribution was: doctor, 15.6%; midwife, 70%; community health officer (CHO), 9.1%; no provider, 5.3%. Women from lower socio-demographic categories were more likely to report midwife or CHO. Report of CHO vs. no provider was positively associated with maternal services (P < 0.01). Report of doctor or midwife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…It is encouraging to note that all our study participants received care from either doctors or midwives, as is the situation in some advanced settings [ 24 ]. One previous study also reported that about 86 % of rural antenatal attendants in Ghana receive care from either midwives or doctors, and that women receiving antenatal care from these categories of health workers were more likely to have skilled attendance at delivery and post-natal care [ 25 ]. It should be noted however, that in other parts of the country especially in rural areas, like many sub-Saharan African countries, ANC clients are also seen by other health workers apart from doctors and midwives.…”
Section: Discussionmentioning
confidence: 99%
“…It is encouraging to note that all our study participants received care from either doctors or midwives, as is the situation in some advanced settings [ 24 ]. One previous study also reported that about 86 % of rural antenatal attendants in Ghana receive care from either midwives or doctors, and that women receiving antenatal care from these categories of health workers were more likely to have skilled attendance at delivery and post-natal care [ 25 ]. It should be noted however, that in other parts of the country especially in rural areas, like many sub-Saharan African countries, ANC clients are also seen by other health workers apart from doctors and midwives.…”
Section: Discussionmentioning
confidence: 99%
“…), as do those in rural areas (Arthur ; Atunah‐Jay et al . ). Some studies demonstrate a positive relationship between a woman's age and ANC usage (Addai ; Doku et al .…”
Section: Introductionmentioning
confidence: 97%
“…Other studies that have analyzed the skilled health personnel category revealed that women who were attended to by midwives, nurses and doctors were far less likely to experience infant mortality compared to those attended to by relatives [38]. Studies on the relationship between antenatal provider, postnatal provider type and maternal care and infant mortality have been comprehensively explored [21,39], however studies on the influence of type of birth attendant on infant mortality have ill been carried out. It is necessary for other variables such as the length of practice of health service providers to be explored to provide more robust explanations.…”
Section: Discussionmentioning
confidence: 99%